Satellite Image Denoising Using Local Spayed and Optimized Center Pixel Weights - Pala Mahesh Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Now a day’s digital image processing applications are widely used in various fields such as medical, military, satellite, remote sensing and even web applications also. In any application image denoising is a challenging task because noise removal will increase the digital quality of an image and will improve the perceptual visual quality. In this paper we proposed a new method “local spayed and optimized center pixel weights (LSOCPW) with non local means” to improve the denoising performance of digital color image sequences. Simulation results show that the proposed method has given the better performance when compared to the existing algorithms in terms of peak signal to noise ratio (PSNR) and mean square error (MSE).DOI:http://dx.doi.org/10.11591/ijece.v4i5.6624